2019
DOI: 10.1158/1055-9965.epi-19-0626
|View full text |Cite
|
Sign up to set email alerts
|

Serum miR-223: A Validated Biomarker for Detection of Early-Stage Non–Small Cell Lung Cancer

Abstract: Background: The published circulating miRNA signatures proposed for early-stage non-small cell lung cancer (NSCLC) detection are inconsistent and difficult to replicate. Reproducibility and validation of an miRNA simple signature of NSCLC are prerequisites for translation to clinical application.Methods: The serum level of miR-223 and miR-29c, emerging from published studies, respectively, as a highly sensitive and a highly specific biomarker of early-stage NSCLC, was measured with droplet digital PCR (ddPCR) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 52 publications
0
16
0
Order By: Relevance
“…Yang et al 31 examined the role of serum miR‐223 in NSCLC diagnosis and the AUC was reported to be 0.740 (95% CI: 0.653‐0.816), while the sensitivity and specificity values were not reported. D'Antona et al 32 proposed new aspects of miR‐223 diagnostic performance in patients with NSCLC. In the mentioned study, the AUC was reported to be 0.808 (95% CI: 0.712‐0.884), the sensitivity was 74.3 (95% CI: 56.7‐87.5), and the specificity was 78.2 (95% CI: 65.0‐88.2) 32 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yang et al 31 examined the role of serum miR‐223 in NSCLC diagnosis and the AUC was reported to be 0.740 (95% CI: 0.653‐0.816), while the sensitivity and specificity values were not reported. D'Antona et al 32 proposed new aspects of miR‐223 diagnostic performance in patients with NSCLC. In the mentioned study, the AUC was reported to be 0.808 (95% CI: 0.712‐0.884), the sensitivity was 74.3 (95% CI: 56.7‐87.5), and the specificity was 78.2 (95% CI: 65.0‐88.2) 32 …”
Section: Discussionmentioning
confidence: 99%
“…D'Antona et al 32 proposed new aspects of miR‐223 diagnostic performance in patients with NSCLC. In the mentioned study, the AUC was reported to be 0.808 (95% CI: 0.712‐0.884), the sensitivity was 74.3 (95% CI: 56.7‐87.5), and the specificity was 78.2 (95% CI: 65.0‐88.2) 32 …”
Section: Discussionmentioning
confidence: 99%
“…Duplicates also increase the sensitivity in detecting low abundance targets, as data from duplicates can be summed up, increasing the number of measured events. Digital PCR has been shown to have the potential for developing diagnostic and prognostic tests based on miRNA measurements [ 75 , 124 , 125 , 126 , 127 , 128 , 129 , 130 ]. However, like qPCR, digital PCR needs miRNA extraction and reverse transcription and therefore some of the drawbacks of qPCR remain the same.…”
Section: Indirect Methods For Mirna Measurement Relying On Rna Exmentioning
confidence: 99%
“…In 2019 miR-223 was validated as a reproducible, effective serum biomarker of early-stage non-small-cell lung cancer using ddPCR technology [ 75 ]. A recent study from Detassis and colleagues demonstrated that miR375-3p distinguishes low-grade neuroendocrine from non-neuroendocrine lung tumors in FFPE samples [ 76 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, these results, among those from other studies [120,121], need proper validation before they can prove their benefit. In a recent study, miR-223 has been validated as an effective and reproducible serum biomarker of early stage NSCLC by using digital-droplet PCR technology [122]. Li et al (2017) identified in a prospective study, using RT-qPCR on plasma samples from 71 patients (41 ALK-positive), a panel of three circulating miRNAs that can discriminate between patients diagnosed with ALK-positive and ALK-negative lung cancers.…”
Section: Circulating Noncoding Rnasmentioning
confidence: 99%